2022
DOI: 10.1111/vcp.13108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 0.3% cholesterol diet and a 20% fat diet on plasma lipids and lipoproteins in Quaker parrots (Myiopsitta monachus)

Abstract: Background Lipid disorders are common in captive psittacine birds, but associated changes in blood lipids and lipoproteins have not been well characterized. The Quaker parrot is prone to dyslipidemia and has been extensively used as an experimental model. Objectives We aimed to study the effects of a 0.3% cholesterol diet and a 20% fat diet on plasma lipids and lipoproteins in Quaker parrots. Methods Two crossover studies were performed with each diet. During each study, 12 parrots were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The 0.3% cholesterol diet leads to profound dyslipidemia in Quaker parrots, with broad changes to the plasma lipidome. 21 It was thought that statin effects would be more evident in hypercholesterolemic and dyslipidemic parrots, but no effect was observed in this investigation with either diet. Statins are inhibitors of cholesterol synthesis, thereby limiting endogenous cholesterol production, whereas exogenous cholesterol was provided to the Quaker parrots through dietary supplementation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The 0.3% cholesterol diet leads to profound dyslipidemia in Quaker parrots, with broad changes to the plasma lipidome. 21 It was thought that statin effects would be more evident in hypercholesterolemic and dyslipidemic parrots, but no effect was observed in this investigation with either diet. Statins are inhibitors of cholesterol synthesis, thereby limiting endogenous cholesterol production, whereas exogenous cholesterol was provided to the Quaker parrots through dietary supplementation.…”
Section: Discussionmentioning
confidence: 58%
“…The cholesterol diet caused some profound changes in the lipidome, but these results were already reported in previous studies and were similar in the current study. 15,21 As these changes were not the purpose of this study and were previously reported, they were not reiterated here.…”
Section: Resultsmentioning
confidence: 74%
“…Given that seed-based diets are known to be unbalanced for psittacine birds and often high in fats [ 43 ], this nutritional imbalance may be a predisposing factor for acquiring xanthogranulomatous diseases, as stated before [ 28 ]. In contrast, recently published experimental studies in Monk Parakeet ( Myiopsitta monachus ) provide some evidence that in the genesis of atherosclerotic lesions, cholesterol concentration of the diet is more important than the overall fat content [ 44 ]. Lipometabolic disorders are suspected to be the main reason for the pathogenesis of disseminated coelomic xanthogranulomatosis, since concurrent atherosclerotic lesions were seen [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%